2014
DOI: 10.1097/fjc.0000000000000109
|View full text |Cite
|
Sign up to set email alerts
|

Scutellarin Inhibits High Glucose–induced and Hypoxia-mimetic Agent–induced Angiogenic Effects in Human Retinal Endothelial Cells Through Reactive Oxygen Species/Hypoxia-inducible Factor-1α/Vascular Endothelial Growth Factor Pathway

Abstract: Scutellarin inhibits hypoxia-induced and moderately high glucose-induced proliferation and vascular endothelial growth factor (VEGF) expression in human retinal endothelial cells (HRECs); thus, it could be a potential therapy for diabetic retinopathy. However, how scutellarin inhibits VEGF is unknown. In our study, HRECs were treated with high glucose and/or hypoxia-mimetic agent cobalt chloride to stimulate cell proliferation, migration, and angiogenesis, and the effects of scutellarin on these processes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Evidence suggests that curcumin and resveratrol may have potential in the treatment of several ocular diseases [39,40]. Scutellarin inhibits retinal angiogenesis through disturbing ROS/HIF-1α/VEGF pathway [27]. In addition, EGCG alleys ocular neovascularization and vascular permeability, congruently accompanying MMP-9 suppression and VEGF activation [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence suggests that curcumin and resveratrol may have potential in the treatment of several ocular diseases [39,40]. Scutellarin inhibits retinal angiogenesis through disturbing ROS/HIF-1α/VEGF pathway [27]. In addition, EGCG alleys ocular neovascularization and vascular permeability, congruently accompanying MMP-9 suppression and VEGF activation [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, they have not been proven effective in randomized, controlled trials. Natural products may serve as specific, efficacious, and affordable agents for a potential DR therapy [26,27,28]. Epigallocatechin-3-gallate (EGCG) inhibits ocular neovascularization and vascular permeability via suppression of MMP-9 and VEGF activation [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retinal Müller cells treated with no glucose for 24 hours resulted in a decrease in cell viability, however high glucose (30mM) increased cell viability [11]. Previous studies on primary human retinal endothelial cells show that high glucose increased cell viability [14,15]. The differences in our findings compared to those published are likely due to inter-species differences (human vs rhesus monkey) as well as the transformation of the rhesus monkey retinal endothelial cells compared to the primary human line reported by our colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…Vellanki et al, 2016 showed that both high and low glucose treatments resulted in an increase in VEGF secretion into cell medium from rat and human müller cells [11]. Primary human retinal endothelial cells show that high glucose stimulates VEGF expression [14,15] and Human Umbilical Vein Endothelial Cells (HUVEC) treated with high glucose (25mM/L) resulted in a decrease in VEGF secretion in cell medium. This contrasting effect to our reports may be due to the difference in cell type and exposure time compared to our rhesus monkey cell line [17].…”
Section: Discussionmentioning
confidence: 99%